Aboveground and belowground biomass and stem density from Spartina anglica - Koop-Jakobsen, Ketil (PANGAEA, 2023)
Aboveground and belowground biomass data and stem density data from a mesocosm experiment with salt marsh vegetation from the low marsh dominated by Elymus athericus and pioneer zone dominated by Spartina anglica. The data is endpoint measurements of biomass and stem density of low marsh and high marsh vegetation after 100 days of incubation in a mesocosm experiment with increased temperature and CO2 treatments. Altogether 12 mesocosms were used. There were 4 treatments with 3 replicates in each. Each mesocosm had 1 sample with low marsh vegetation and 1 sample with pioneer zone vegetation.
Keywords: Biomass; Elymus; organic matter; pioneer zone; plants; salt marsh; Spartina; Vegetation; Wadden Sea